Comparatıve evaluatıon of whıte spot lesıon formatıon and shear bond strength of braces bonded ındırectly wıth and wıthout etchıng masks - Panagiotou, Aristeidis (My University, 2015)
Comparative Evaluation Of White Spot Lesion Formation And Shear Bond Strength Of Braces Bonded Indirectly With And Without Etching Masks Aim: To determine the shear bond strength (SBS) of the braces bonded indirectly on the enamel surfaces with and without etching masks and to evaluate the formation of white spot lesions around these braces. Materials and Methods: Eighty premolar teeth were collected from patients whose teeth needed to be extracted for orthodontic treatment purposes and were mounted on acrylic plates. Then, they were randomly divided into two equal groups. In group A, etching masks were used, while in group B, etching masks were not used. Another examiner, who did not know the purpose of the study, performed the etching and indirect bonding of the brackets. Following indirect bonding, all specimens were immersed in a demineralization solution for 96 hours at 370C. The extent of demineralization in each group was assessed by using quantitative light-induced fluorescence (QLF). QLF images of all specimens were taken just before the immersion in the demineralization solution and after 96 hours and fluorescence loss (ΔF) was recorded. SBS values were determined by using universal testing machine. The enamel surfaces and the brackets were examined under a stereomicroscope and any remaining adhesive was assessed and recorded using the adhesive remnant index (ARI). Results: Before demineralization, there was no significant difference in the ΔF between the two groups (p>0,05). However, after demineralization, Group B had a significantly higher value of ΔF compared to group A (p<0,05). As far as the total loss of ΔF is concerned, no statistically significant difference was found between the two groups (p>0,05). Moreover, no significant differences in SBS and ARI scores between the two groups were detected (p>0,05). Conclusion: Usage of etching mask did not decrease the formation of WSL. Key words: Indirect Bonding, Etching Mask, White Spot Lesions, Shear Bond Strength, ARI.
Keywords: Ortodonti